Healthcare workers’ perspectives on barriers and facilitators to referral to type 2 diabetes prevention programmes: a systematic review - Patricia M Kearney; Sheena M Mc Hugh; Sarah Cotterill; Fiona Riordan; Jennifer A Pallin; Clair Haseldine; Grainne O’Donoghue (BMJ Open)
Objectives Diabetes is a growing global health concern. International guidelines recommend referral to diabetes prevention programmes (DPPs) for those at high risk of type 2 diabetes. However, many of those eligible to participate in DPPs are not referred. Healthcare workers (HCWs) are pivotal to the referral processes. This study aimed to identify, appraise and synthesise barriers and facilitators to referral to DPPs from the perspective of HCWs.Design Systematic review using the best-fit framework synthesis.Data sources MEDLINE, Embase, CINAHL, PsychINFO, Web of Science and Scopus were searched from January 1997 to July 2023.Eligibility criteria Qualitative, quantitative and mixed methods primary studies exploring HCWs’ perspectives of barriers and facilitators to referral to DPPs.Data extraction and synthesis One author screened, extracted and appraised the literature while a second author independently verified at least a 20% sample at each stage. Quality was assessed using the Mixed Methods Appraisal Tool. The best-fit framework approach was used to synthesise the evidence with the Theoretical Domains Framework as the a priori framework.Results Of 9998 studies identified, 31 met the inclusion criteria, with a further six identified from reference and citation searching. Barriers and facilitators were coded to 11 of the 14 TDF domains and to another category ‘Expectation of Patient Barriers’. The most frequently occurring domains for both barriers and facilitators were Environmental Context and Resources, Expectation of Patient Barriers and Knowledge. HCWs felt that clear easy referral pathways to the programmes and additional staff or resources were essential to improve referral. HCWs’ were concerned that attending the DPP would place a (time and/or financial) burden on their patients which left them conflicted about referral. HCWs lacked knowledge of the effectiveness, availability and accessibility of DPPs.Conclusions Future strategies to improve referral to DPPs should include clear referral pathways and the resourcing of referral. Strategies are also needed to build awareness of DPPs and to address concerns among HCWs about their patients.